High temperature electrical conductivity due to small polaron hopping motion in DNA molecules - Triberis, G.P.; Karavolas, V.C.; Simserides, C.D. (Journal of Physics: Conference Series, 2005)
We present a small polaron hopping model to interpret the high-temperature electrical conductivity measured along the DNA molecules. The model takes into account the one-dimensional character of the system and the presence of disorder in the DNA double helix. The experimental data for the lambda phage DNA (λ-DNA) and the poly(dA)-poly(dT) DNA follow nicely the theoretically predicted behavior leading to realistic values of the maximum hopping distances supporting the idea of multiphonon-assisted hopping of small polarons between next nearest neighbors of the DNA molecular "wire".